Hz. Peygamber’in ve hulefa-i raşidin’in sünnetine sarılmayı emreden hadisin değerlendirilmesi - Güşen, Seyit Ali (My University, 2007)
Seyit Ali GÜŞEN, Hz. Peygamber ve Hulefâ-i Râşidîn’in Sünnetine Sarılmayı Emreden Hadisin Değerlendirmesi İhtiva ettiği konular itibarıyla pek çok İslâmî ilim dalında kendine ait bir yer bulan “Hulefâ-i râşidîn’in sünneti” hadisi, hadis kitaplarında sünnete teşvik ve bidatlardan sakındırma; fıkıh kitaplarında sahabe kavlinin değeri; kelam kitaplarında Hulefâ-i râşidîn’in fazileti; ahlâk kitaplarında Allah korkusu gibi çeşitli konularda delil olarak zikredilmiştir. Tek bir sahâbîden nakledilmesine rağmen geçmiş alimler tarafından sıhhati konusunda herhangi bir itiraza ve eleştiriye uğramadan delil olarak kullanılan bu hadis günümüzde bazı tenkidlere maruz kalmıştır. Bu çalışmada hadiste yer alan halife ve raşid kavramları araştırılmış ve “Hulefâ-i râşidîn” teriminin tarihi incelenmiştir. Hadisin sened ve metni incelerek sahih olduğu kanaatine varılmıştır. Hadisin kelam, fıkıh ve hadis bilimlerinde önemli bir yere sahip olduğu görülmüştür.

EVALUATION OF THE HADITH THAT ORDERS TO FOLLOW THE SUNNAH OF THE PROPHET AND AL-KHULEFA AL-RASHIDEEN The Hadith of “sunnah of the Prophet and al-Khulefa al-Rashideen”, which has found place in many Islamic disciplines because of its content, was mentioned as a proof in Hadith books to exhort to the sunnah and forbid from the bid’ah; in Fiqh books in the context of the proof-value (hujjyyah) of sahabi's opinion; in Kalam books in the subject of the virtue of al-Khulefa al-Rashideen; in Morality books in the context of taqwa. In spite of this hadith comes to us from only a sahabi transmitter and there were not any criticism by the ancient scholars on it; at the present time this hadith is criticized by some scholars. This work studies comprehensively the terms of “Khalifah” and “Rashid”; also examines the history of the term of “al-Khulefa al-Rashideen” which takes part in the hadith. As a conclusion this study confirms that the hadith is correct (sahih) with its text (matn) and chain of narration (sanad) and shows this hadith has important part in the Islamic sciences, not only for the Hadith discipline, but also for the Fiqh and Kalam disciplines.
Keywords: Hadis; İslam Dini